Social Support for Wives in Advanced Studies - Kusumadewi, Icha (Universitas Muhammadiyah Metro, 2017)
This study aimed to analyze social support on the wife who studies the master. The approach employed in this study was qualitative phenomenological. Samples in this study as many as two respondents, female students master, career woman, and married. In addition, there were secondary informants that comes from the husband, classmates, and coworkers subject. There are 6 secondary informants this research. Data were collected used interviews and observation. Forms interviews used in this study are free guided interviews and using participant observation. The validity of the data in this study using triangulation of sources and methods. The study found that two subjects in the lead role as a wife, staff, and students were able to run third that role with the help of others. But despite the help of others, this study provides new findings that the success of subjects affected their spiritual support that makes the subject able to survive to make the subject is able to do their job